The Teacher’s Obstacle in Applying Merdeka Curriculum - Nasir, Vebiyanti; Muhamad, Sariwati (International Journal of Education, Information Technology, and Others, 2025)
Curriculum Merdeka is new curriculum that the government applied in the school. Curriculum Merdeka also new for the teacher to understand and to apply it at the class. This research aims to know the teachers’ obstacles in applying Merdeka Curriculum. As a new curriculum, of course the teachers will faced many obstacles. This research also aims to know how the teachers find the solutions to fix the obstacles they faced. This research sites at SMA Negeri 5 Kota Tidore Kepulauan. The participant of this research consists of all the teachers in class X that have implementing curriculum of Merdeka Belajar. Technique of collecting the data is using questionnaire and analyzing the data by organized the data, then interpreted the data from google form, and the last is presented the data into the research result. The result of this research is there are many obstacles that the teachers at SMA Negeri 5 Kota Tidore Kepulauan faced. They are administrative difficulties such as analyzing teaching modules and assessment, and the implementation of Curriculum Merdeka such as not utilizing the technology and not implementing differentiated learning.